2020
DOI: 10.1590/0102-311x00193919
|View full text |Cite
|
Sign up to set email alerts
|

Efetivação da Lei Menino Bernardo pelas redes de proteção e de atendimento a crianças e adolescentes

Abstract: Embora muitos países estejam implementando leis que proíbem o uso de violência física como pretensa prática educativa, a Organização Mundial da Saúde indica que a efetivação dessas leis ainda é um desafio. Objetivou-se, portanto, verificar se as redes de proteção e de atendimento a crianças e adolescentes em situação de risco estão organizadas para efetivar a Lei Menino Bernardo (Lei nº 13.010/2014). Por meio de uma abordagem qualitativa e exploratória, foram entrevistados 16 profissionais de diferentes serviç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
12

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 28 publications
0
4
0
12
Order By: Relevance
“…Most of the selected articles address child abuse in a general manner 24,26,[29][30][31][32][34][35][36][39][40][41][42][43][44][45][46][47] without specifying the type of violence. In the studies that reported type of violence, the most common types were physical 27,28,37 and sexual 25,33,38 violence. The literature shows that while there are various types of maltreatment (physical, psychological, sexual, institutional violence, and neglect 14,49 ), professionals tend to be more aware of physical violence and view it differently as it leaves visible marks on the victim's body or triggers feelings of disgust, especially in cases of sexual violence, which can have an even greater emotional impact on professionals 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the selected articles address child abuse in a general manner 24,26,[29][30][31][32][34][35][36][39][40][41][42][43][44][45][46][47] without specifying the type of violence. In the studies that reported type of violence, the most common types were physical 27,28,37 and sexual 25,33,38 violence. The literature shows that while there are various types of maltreatment (physical, psychological, sexual, institutional violence, and neglect 14,49 ), professionals tend to be more aware of physical violence and view it differently as it leaves visible marks on the victim's body or triggers feelings of disgust, especially in cases of sexual violence, which can have an even greater emotional impact on professionals 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is worth noting that one of the studies 37 suggests that combating violence goes beyond improvements in professional training, also involving parent education and public awareness campaigns. Another study 46 highlights that strengthening parent-child relationships and actions that bring together families and communities are factors that facilitate the work of professionals dealing with child violence and promoting child protection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A punição corporal (PC) em crianças e adolescentes é considerada um mau-trato físico, que se manifesta de diferentes formas e em inúmeros contextos sociais, com repercussões nas saúdes física e mental dos filhos. Fatores como a não notificação de casos, não sistematização de dados, falta de preparo e de capacitação de profissionais que lidam com esse fenômeno, fortalecem tal prática e dificultam intervenções (AZEVEDO; BAZON, 2021a;LONGO, 2005;PICCININI et al, 2003;TRINDADE;HOHENDORFF, 2020;VITOLO et al, 2005).…”
Section: Introductionunclassified